Two New Compounds Containing Pyridinone or Triazine Heterocycles Have Antifungal Properties against Candida albicans - Laura Mena; Muriel Billamboz; Rogatien Charlet; Bérangère Desprès; Boualem Sendid; Alina Ghinet; Samir Jawhara (MDPI AG, 2022)
Candidiasis, caused by the opportunistic yeast Candida albicans, is the most common fungal infection today. Resistance of C. albicans to current antifungal drugs has emerged over the past decade leading to the need for novel antifungal agents. Our aim was to select new antifungal compounds by library-screening methods and to assess their antifungal effects against C. albicans. After screening 90 potential antifungal compounds from JUNIA, a chemical library, two compounds, 1-(4-chlorophenyl)-4-((4-chlorophenyl)amino)-3,6-dimethylpyridin-2(1H)-one (PYR) and (Z)-N-(2-(4,6-dimethoxy-1,3,5-triazin-2-yl)vinyl)-4-methoxyaniline (TRI), were identified as having potential antifungal activity. Treatment with PYR and TRI resulted in a significant reduction of C. albicans bioluminescence as well as the number of fungal colonies, indicating rapid fungicidal activity. These two compounds were also effective against clinically isolated fluconazole- or caspofungin-resistant C. albicans strains. PYR and TRI had an inhibitory effect on Candida biofilm formation and reduced the thickness of the mannan cell wall. In a Caenorhabditis elegans infection model, PYR and TRI decreased the mortality of nematodes infected with C. albicans and enhanced the expression of antimicrobial genes that promote C. albicans elimination. Overall, PYR and TRI showed antifungal properties against C. albicans by exerting fungicidal activities and enhancing the antimicrobial gene expression of Caenorhabditis elegans.